ANALISIS KEMAMPUAN BERPIKIR TINGKAT TINGGI (HIGH ORDER THINGKING SKILLS) MAHASISWA DALAM MEMECAHKAN MASALAH MATERI SUHU DAN KALOR PADA MATA KULIAH FISIKA UMUM T.A 2019/2020 - ERNI KUSRINI SITINJAK (LP2MTBM MAKARIOZ, 2020)
This research aims to determine the ability to think high level of student education study Program of physics Universits HKBPNommensen Pematangsiantar school year 2109/2020. This type of research is quantitative research. The population in thisstudy is the entire education student at the University of HKBP Nommensen Pematangsiantar semester 1 year 2019/2020,amounting to 82 people consisting of A class of 42 people and class B a number of 40 people. The research sample is classB a number of 40 people. In the study samples provided cognitive instrument test categories C4 (analyze), C5 (Evaluate)and C6 (create) are included in the category of Test High Order Thinking Skills (HOTS). The results gained from the studythat the mathematics education students have the ability of HOTS level analyze, evaluate and create are in category enoughwith a percentage achievement of 51%-75%.